The role of post translational modifications in the regulation of binding of linker histone Hho1 to chromatin in Saccharomyces cerevisiae - Sharma, Pankaj (University of the Free State, 2015)
The eukaryotic genome is functionally organized into a highly ordered nucleoprotein structure, chromatin. Apart from the four nucleosomal core histones, the linker histone is pivotal to fluidity and compaction of chromatin. Yeast, a single cell eukaryote, has a short nucleosomal repeat length, and possesses a structurally unique H1. This thesis is an attempt to study the influence of post translational modifications in regulating the interactions of yeast linker histone with chromatin. Chapter 1 gives a broad overview of available literature. Chapter 2 presents the results from cloning, expression, purification and partial characterization of Hho1p. The physiochemical characteristics of recombinant protein were studied with a view to perform subsequent purification of native Hho1p from yeast strains. The solubility and precipitation of rHho1p were explored under several conditions. Unlike canonical linker histone, Hho1p was found to be insoluble in Perchloric acid. Chapter 3 comprises generation and characterization of polyclonal antibody against Hho1p. Affinity purified monospecific antibodies were used to optimize semi-quantitative Western blotting. Preliminary results from Western blotting analysis suggest that Hho1p is capable of oligomeric interactions. Chapter 4 presents results for optimization of conditions for Hho1p extraction from yeast cells or nuclei. For nuclear extract preparation, a standard method and its rapid variation, developed to limit Hho1p proteolysis, were used. The acid extraction of Hho1p from nuclei followed by its purification by reverse phase chromatography provided low yield for downstream analysis. However, sufficient quantities of native Hho1p could be extracted from cell lysate using affinity matrices prepared with the monospecific αHho1p antibodies generated in-house. Several novel post translational modification sites and binding partners of Hho1p were identified from both logarithmic and stationary phase of yeast cell growth, providing an insight into the stage specific regulation of Hho1p chromatin binding.
Thesis (Ph.D. (Biotechnology))--University of the Free State, 2015
Keywords: Saccharomyces cerevisiae; Chromatin; Histones; Eukaryotic cells; Yeast; Post-translational modification